(untitled) (World Economics and Finance Bulletin, 2026)
In the current digital economy, the volume and complexity of audit audits are increasing dramatically. Traditional audit methods have limited capabilities for quickly and accurately analyzing large amounts of data. Therefore, the integration of artificial intelligence technologies into audit processes is one of the pressing issues. This article comprehensively analyzes the issues of increasing the efficiency of using artificial intelligence technologies in audit audits. In the conditions of the modern digital economy, audit processes are characterized by the complexity of working with large amounts of data, identifying and assessing risks. The limitations of traditional audit approaches, in particular, their subjectivity and their reliance on selective inspection, increase the need to introduce artificial intelligence technologies. The study examined the role of artificial intelligence in audit activities, including its capabilities in risk assessment, fraud detection, analyzing large amounts of data, and automating audit processes. It also substantiated the importance of artificial intelligence technologies in transferring audit processes to proactive management, ensuring real-time monitoring, and optimizing decision-making processes.